2019
DOI: 10.1021/acs.est.9b01196
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Phase State and Its Link to Chemical Composition and Liquid Water Content in a Subtropical Coastal Megacity

Abstract: Particle phase state plays a key role in gas-particle partitioning, heterogeneous and multiphase reactions, and secondary aerosol formation. In this work, the rebound fraction and chemical composition of submicron particles were simultaneously measured to investigate the particle phase state and its link to chemical composition in a subtropical coastal urban city (Shenzhen, China). Submicron particles were found to be in the liquid state for most of the measurement period in spring. During the sampling time, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 72 publications
(141 reference statements)
2
53
1
Order By: Relevance
“…This work paves the way for implementing a more accurate representation of multiphase chemistry of different complex systems on the lines of explicit representation of IEPOX SOA. Multiphase chemistry of other dominant SOA apart from IEPOX SOA, such as monoterpene-derived SOA and ONs derived from both isoprene and monoterpenes, is not incorporated in CMAQ v5.2.1 (Pye et al, 2018;Slade et al, 2019) and should be a focus of future work. This work showed that organic water fraction is the biggest driver of viscosity, though the water abundance was set at a constant 10 % of the inorganic water content to better reflect observed concentrations of organic water during daylight hours relevant to IEPOX SOA chemistry.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
“…This work paves the way for implementing a more accurate representation of multiphase chemistry of different complex systems on the lines of explicit representation of IEPOX SOA. Multiphase chemistry of other dominant SOA apart from IEPOX SOA, such as monoterpene-derived SOA and ONs derived from both isoprene and monoterpenes, is not incorporated in CMAQ v5.2.1 (Pye et al, 2018;Slade et al, 2019) and should be a focus of future work. This work showed that organic water fraction is the biggest driver of viscosity, though the water abundance was set at a constant 10 % of the inorganic water content to better reflect observed concentrations of organic water during daylight hours relevant to IEPOX SOA chemistry.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
“…The OA volatility is intrinsically related to particle phase state that plays an important role in affecting heterogeneous reactions and the formation of cloud condensation nuclei. Particle phase states have been measured by using three-arm impactor (Liu et al, 2017;Liu et al, 2019) and polarization lidar (Tan et al, 2020) in China in recent years. The results showed that particles are generally in liquid state throughout the year in south China, while there is a transition from semisolid to liquid state as RH increases above 60% in winter in NCP.…”
Section: ;mentioning
confidence: 99%
“…Compared with laboratory experiments, the oxidation pathways and oxidants are far more complex in ambient air, and the oxygenated products can be composed of hundreds or even thousands of species with a wide range of volatilities. Previous field observations on volatility distributions of OA have mainly been focused on Europe and the US under low NO x levels (Xu et al, 2016;Louvaris et al, 2017a;Saha et al, 2017;Kostenidou et al, 2018). Lee et al (2011a) found that NO x can have a large impact on the volatility of SOA in a chamber experiment, suggesting that the OA volatilities in high-NO x and high particulate-matter (PM) environments, e.g., the North China Plain (NCP), need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The OA volatility is intrinsically related to particle phase state, which plays an important role in affecting heterogeneous reactions and the formation of cloud condensation nuclei. Particle phase states have been measured by using a three-arm impactor (Liu et al, 2017(Liu et al, , 2019 and polarization lidar (Tan et al, 2020) in China in recent years. The results showed that particles are generally in liquid state throughout the year in south China, while there is a transition from semisolid to liquid state as RH increases above 60 % in winter in the NCP.…”
Section: Introductionmentioning
confidence: 99%